2016
DOI: 10.1097/mcp.0000000000000258
|View full text |Cite
|
Sign up to set email alerts
|

Pleural biopsies in undiagnosed pleural effusions; Abrams vs image-guided vs thoracoscopic biopsies

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms However this service is not universally available and may be unsuitable for some patients.Image-guided cutting-needle biopsies under computed tomography or ultrasound guidance have high diagnostic rates and are useful in a wide patient population. The main role of Abrams biopsies is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…Unfortunately, cytological yield is low in MPM, and biopsies are usually required to confirm the diagnosis and identify the histological sub-type [1,35,38]. Biopsies can be obtained percutaneously under radiological guidance, or under direct vision at thoracoscopy, either as a local anaesthetic procedure (medical thoracoscopy) or as a surgical intervention (video-assisted thoracoscopic surgery (VATS)) [39]. The choice of biopsy technique will vary between patients depending on the distribution and morphology of their disease, their suitability for surgery or invasive procedures and the availability of services [39].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, cytological yield is low in MPM, and biopsies are usually required to confirm the diagnosis and identify the histological sub-type [1,35,38]. Biopsies can be obtained percutaneously under radiological guidance, or under direct vision at thoracoscopy, either as a local anaesthetic procedure (medical thoracoscopy) or as a surgical intervention (video-assisted thoracoscopic surgery (VATS)) [39]. The choice of biopsy technique will vary between patients depending on the distribution and morphology of their disease, their suitability for surgery or invasive procedures and the availability of services [39].…”
Section: Diagnosismentioning
confidence: 99%
“…Biopsies can be obtained percutaneously under radiological guidance, or under direct vision at thoracoscopy, either as a local anaesthetic procedure (medical thoracoscopy) or as a surgical intervention (video-assisted thoracoscopic surgery (VATS)) [39]. The choice of biopsy technique will vary between patients depending on the distribution and morphology of their disease, their suitability for surgery or invasive procedures and the availability of services [39]. The evidence for the various biopsy approaches has been discussed elsewhere and is not included in this article [39].…”
Section: Diagnosismentioning
confidence: 99%
“…Although thoracoscopic and video-assisted pleural biopsy have high specificity as minimally invasive procedures, they are not well tolerated by some patients, and may not be available in all hospitals (Bibby and Maskell 2016). Therefore, novel noninvasive methods able to differentiate MPEs from benign effusions are required.…”
mentioning
confidence: 99%
“…As previously noted, TUS may also be used to guide more advanced pleural interventions, such as pleural biopsies or medical thoracoscopy. It has been demonstrated that this provides similar safety benefits by reducing the incidence of haemorrhage, pneumothorax and visceral injury, while also facilitating a high diagnostic yield of >90% [16][17][18][19][20][21].…”
mentioning
confidence: 99%